1996
DOI: 10.1161/01.cir.94.3.445
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Air-Filled Albumin Microbubble and Red Blood Cell Rheology in the Human Myocardium

Abstract: There is close correlation between air-filled albumin microbubbles and RBC rheology in the human myocardium. The use of these microbubbles in the cardiac catheterization laboratory could, therefore, provide further insights into myocardial blood flow/myocardial blood volume relations in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 23 publications
0
22
0
2
Order By: Relevance
“…These microbubbles are injected intravenously and travel through the circulation with rheological properties similar to erythrocytes, enhancing bloodto-tissue contrast [5]. Current FDA-approved microbubble contrast agents are based on a lipid monolayer or albumin shell encapsulating a high-molecular weight gas [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…These microbubbles are injected intravenously and travel through the circulation with rheological properties similar to erythrocytes, enhancing bloodto-tissue contrast [5]. Current FDA-approved microbubble contrast agents are based on a lipid monolayer or albumin shell encapsulating a high-molecular weight gas [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Microbubble contrast agents are generally between 1 and 8 m in diameter, allowing uninterrupted passage through capillaries. Previous studies have demonstrated that the rheology of microbubble agents is similar to that of erythrocytes (22,23,34) and behave as purely intravascular flow tracers. Unlike iodinated contrast agents and chelates used for MRI, microbubble agents are not filtered by the kidney.…”
mentioning
confidence: 99%
“…Because the microvascular rheology of the microbubbles used for MCE is similar to that of red blood cells (RBC) [101,102],MCE has been shown to be able to noninvasively and accurately quantify MBF velocity [103].…”
Section: Recent Approaches To the Detection And Quantification Of Cormentioning
confidence: 99%